Red Dragon Pudding (Hylocereus Polyrhizus) on Hemoglobin Levels of Anemia Adolescents - Indah Putri Ramadhanti; Desri Nova H; Debby Ratno Kustanto; Mimi Fitriani (Indonesian Journal of Global Health Research, 2025)
WHO data in 2022 stated that anemia in adolescents aged 13-18 years was 23%, developing countries 53.7% in 2018. Based on the 2023 SKI, anemia in adolescents in Indonesia is quite high, which is 32% at the age of 15-24 years, which has an impact on adolescent health. The iron and vitamin content of dragon fruit affects the process of hemoglobin formation in red blood cells. This study aims to determine the effect of giving dragon fruit pudding on hemoglobin levels in anemic female adolescents. Quantitative research type, Pre-Experimental Design method, One-Group Pretest-Posttest Only Design. The infinite population of all anemic female adolescents in the Koto Lolo Health Center work area, Sungai Penuh City with a purposive sampling technique obtained 16 respondents in 2024. The instrument uses POCT (Easy Touch GCHb Brand) and observation sheets. Data is not normally distributed, using the Wilcoxon test. Univariate analysis obtained the average hemoglobin level before being given dragon fruit pudding was 9,81 + SD 0.832 and after being given dragon fruit pudding was 11,81 + SD 0.758. There was an increase of 2 gr/dl in Hb levels. The results of the bivariate analysis obtained a p value of 0.001 which means (p≤0.05). There is an effect of giving dragon fruit pudding on the hemoglobin levels of anemic adolescent girls in the Koto Lolo Health Center work area in 2024. It is hoped that giving dragon fruit pudding as one of the alternative companion therapy programs to increase Hb levels in anemic adolescent girls